Discovery and SAR of novel series of imidazopyrimidinones and dihydroimidazopyrimidinones as positive allosteric modulators of the metabotropic glutamate receptor 5 (mGlu5). Issue 6 (15th March 2015) - Martín-Martín, María Luz; Bartolomé-Nebreda, José Manuel; Conde-Ceide, Susana; Alonso de Diego, Sergio A.; López, Silvia; Martínez-Viturro, Carlos M.; Tong, Han Min; Lavreysen, Hilde; Macdonald, Gregor J.; Steckler, Thomas; Mackie, Claire; Bridges, Thomas M.; et al.
Graphical abstract